2022
DOI: 10.3390/ijms23169149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimicry of the Rheumatoid Arthritis-Related Immunodominant T-Cell Epitope within Type II Collagen (CII260-270) by the Bacterial L-Asparaginase

Abstract: The etiology of most autoimmune diseases, including rheumatoid arthritis (RA), remains unclear. Both genetic and environmental factors are believed to be involved in pathogenesis. Molecular mimicry is considered one of the mechanisms for the occurrence of autoimmune diseases. The aim of the study was to determine whether the bacterial peptide L-ASNase67-81, which mimics the immunodominant T-cell epitope CII259-273, can induce T-cell reactivity in blood samples from RA patients and healthy subjects through mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…We have already reported that bacterial L-asparaginase can activate the T-cell response in ERA patients through molecular mimicry [24]. As an extension of that study, we report here that this enzyme may also play a role in the B-cell response by modifying immunodominant T-cell epitopes.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…We have already reported that bacterial L-asparaginase can activate the T-cell response in ERA patients through molecular mimicry [24]. As an extension of that study, we report here that this enzyme may also play a role in the B-cell response by modifying immunodominant T-cell epitopes.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, the same ERA patients (n = 12) and healthy subjects (n = 11) who participated in a pre-vious study [24] were enrolled again (Table 1). Moreover, we already had frozen sera from these participants.…”
Section: Patients With Rheumatoid Arthritis and Healthy Subjectsmentioning
confidence: 99%
See 3 more Smart Citations